2020
DOI: 10.4103/ijp.ijp_1001_20
|View full text |Cite
|
Sign up to set email alerts
|

Novel therapeutic approaches toward Hantaan virus and its clinical features’ similarity with COVID-19

Abstract: Zoonotic virus spill over in human community has been an intensive area of viral pathogenesis and the outbreak of Hantaan virus and severe acute respiratory syndrome coronavirus 2 (SARS CoV2) after late December 2019 caused a global threat. Hantaan virus is second to the COVID-19 outbreak in China with seven cases positive and one death. Both RNA viruses have opposite sense as in (−) for Hantaan virus and (+) for SARS CoV2 but have similarity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…Recent studies reported that patients with HFRS who also had COVID-19 had more severe symptoms and longer hospital stays than those with HFRS alone (Singh et al, 2020;Subramaniam et al, 2022). Their study also reported a higher mortality rate among HFRS patients with COVID-19.…”
Section: Introductionmentioning
confidence: 95%
“…Recent studies reported that patients with HFRS who also had COVID-19 had more severe symptoms and longer hospital stays than those with HFRS alone (Singh et al, 2020;Subramaniam et al, 2022). Their study also reported a higher mortality rate among HFRS patients with COVID-19.…”
Section: Introductionmentioning
confidence: 95%